Effect of time of harvest on the incidence of Fusarium spp. in kernels of silage corn - Xue, Allen; Ma, Baoluo; Clear, Randall; Vigier, Bernard (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2005)
AbstractThe effect of time of harvest (at 75, 50 and 25% of milkline) on the incidence of kernel-borne Fusarium spp. was examined in four silage corn (Zea mays) hybrids (MAIZEX Leafy 4, NK BRAND Enerfeast 1, PIONEER 37M81 and MYCOGEN TMF94) in Ottawa, Ontario, in 2001 and 2002. Eleven Fusarium species were isolated over the 2 yr. Fusarium subglutinans was the dominant species recovered from 28.8% of the kernels. Other frequently isolated species included F. oxysporum (2.6%), F. graminearum (2.5%), F. proliferatum (0.3%) and F. sporotrichioides (0.2%). Trace amounts (< 0.1%) of the remaining six species, F. avenaceum, F. crookwellense, F. culmorum, F. equiseti and F. solani, were recovered from the kernels. When the kernels were harvested at 75, 50 and 25% of milkline, the incidence of F. subglutinans increased from 20.9 to 26.7 and to 38.7%, respectively; that of F. graminearum increased from 1.7 to 2.9 and to 3.1%; and for the total of the five main Fusarium species it increased from 28.7 to 32.2 and to 42.3%. Incidence of the other species was not affected by harvesting date. Of the four silage corn hybrids, NK BRAND Enerfeast1 had a significantly lower incidence of Fusarium species in kernels than the other hybrids, indicating a genotypic variation in resistance to kernel-borne infection by Fusarium species.